Students, their Protests, and their Organizations. Exploring Old Gaps and New Evidence - Proteasa, Viorel; Andreescu, Liviu (PARTECIPAZIONE E CONFLITTO, 2019)
While introducing the four contributions to the special issue "Students, their protests, and their organizations: exploring old gaps and new evidence", we link them with influential literature on students' protests and their organizations. The 'old gaps' refer to the long-standing divide between two traditions of research in students' collective action: social movements and organizational studies. The 'new evidence' refers to the finding that studentship is not conducive to protests (Oana 2019a), while the father's education is a strong predictor. While the 'agentic' character of studentship is one important presumption behind many arguments making sense of campus unrest, this finding does not invalidate it as such, but rather indicates that selection to higher education, and not campus socialization, may be conducive to this form of political participation.